FND : the Hill channel partner decision - Nanni, Alfred J. (London : Institute of Management Accountants, 2019)
The case centers on FND, a company that specializes in providing data storage solutions to its customers. The company offers two storage solutions, Parallax its premium solution and Herald its second-tier solution. Raphaella Munoz is the director of the Herald division and must strategize on how to increase market penetration and focus within FND on Herald.
Originally Published InNanni, A. J. (2019). FND: The Hill Channel Partner Decision. IMA Education Case Journal, 12(4), Article 3.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Database industry -- Case studies